(untitled) (Bangladesh Journal of Plant Taxonomy, 2014)
Sisyrinchium angustifolium Mill. (Iridoideae, Sisyrinchieae) has been reported as a new record for the flora of Turkey from NE Anatolia, and taxonomic and conservation status of this species are evaluated. Detailed morphological description, leaf and stem anatomical properties, and chromosome numbers are provided. The present chromosome count is the first tetraploid level for this species reported from Eastern Anatolia, Turkey. DOI: http://dx.doi.org/10.3329/bjpt.v21i2.21357 Bangladesh J. Plant Taxon. 21(2): 175-180, 2014 (December)